Rethinking Healthcare Quality and Prestige: Is This a Manager's Number One Problem? - Morales-Burton, Veronica; Lopez-Ramirez, Sofía A. (Frontiers in Public Health, 2022)
Healthcare institutions are organizations driven to provide medical assistance at a certain level of quality service and safety. To achieve the recognition of excellence, these entities can undergo accreditations and comparisons with other institutions of their kind through ranking systems in order to validate patient, organizational, and academic institutional standards. Usually, the goal is to obtain prestige and recognition as well as positive feedback towards the institution, motivating improvement. In this scenario, the manager’s role is to communicate these results and propose strategies to maintain or increase healthcare quality. The following essay discusses the fundamentals of the processes of accreditation and ranking systems, the importance of health managers on the complexity of these processes and on achieving an institution’s goals and vision, but also intends to provide a critical view towards the desire for prestige a hospital envisions within the feedback when its biggest aim should be directed to improve in benefit of the patients and workforce conditions.